Molecular Investigation of E.dispar in Terms of Virulence Factors CP1, CP5 - Khalid Thamir Mattar AL-Shaibani (Journal of Global Pharma Technology, 2018)
The current study included the detection of existence the Parasite E.dispar in 180 samples of feces for stricken patients with diarrhea from revisers to public hospital of Al -Shamia and three primary health centers in the district of Al- Shamia which is subsidiary to Al- Qadisiyah governorate for period of July 2016 till the end of December 2017, only 48 samples containing the Parasite of amoeba with it nourished ,sacked state or both out of 180 sample of feces for stricken patients with diarrhea, the incidence rate of the Parasite of amoeba recorded 26.22%, and the obligation results are submitted to microscopic examination for Molecular examination to Real Time PCR (Taq Man Probe) to specific investigate to the E. dispar and indicate the existence this kind in 31 samples ,with 64.58% rate of the total of 48 obligation samples, after then the obligation samples underwent to molecular testing for E. dispar to investigate about each of the two the predation virulence factors, CP1 and CP5 using SYBER Green Real Time PCR. the current study has shown that the possession E. dispar for the virulence factors malign factor of CP1 using the initiators concern the genes, then proved existence of the CP1 factor in 18 samples of total 31 positive samples for parasite with 58.06% rate . While did not prove existence the gene of the CP5 in the type of E. dispar. Some studies to be positive about that E. dispar coexisted in the intestines of human , while other studies pointed to a lack of clarity about the fact of this type has pathogen or no , because of its ability to bring about (causation ) some focal lesions and harming and make damage in the laboratory living tissues . from this standpoint, the current study come to investigate about two virulence factors of the virulence factors as a step of steps the study which consider the most comprehensive study of the Species E. dispar to show the reality of living of this kind.Keywords: E. dispar, CP1, CP5.